Analysis of the implementation of good governance in the management of organizational culture and work discipline at the communication, informatics, statistics and cryptography service of Banten Province - Mansur, Mansur; MZ, Dede Mohammad Rizal; Sudrajat, Ajat; Wirtadipura, Dian; Fajar, Tubagus Regiasa (Indonesia Auditing Research Journal, 2026)
This study aims to analyze the implementation of good governance principles in managing organizational culture and work discipline at the Department of Communication, Informatics, Statistics, and Encryption of Banten Province. The research employs a qualitative approach with a post-positivist paradigm, using in-depth interviews, observations, and documentation as data collection techniques. Data were obtained from key informants and supporting staff who are directly involved in organizational management and public service delivery. The findings indicate that organizational culture has been directed toward professionalism, transparency, and participation, supported by leadership commitment and the use of digital governance systems. However, gaps remain between expected organizational values and their practical implementation, particularly in terms of consistency, discipline, and internalization of work ethics. The application of work discipline has been supported by digital attendance and performance monitoring systems, yet it still faces challenges related to motivation and compliance. Furthermore, the implementation of good governance principles has contributed to improvements in information transparency and public service performance, although continuous strengthening of human resource capacity and organizational culture is required. This study concludes that effective integration of organizational culture and work discipline plays a crucial role in enhancing good governance practices. Strengthening leadership commitment, internal control mechanisms, and continuous capacity building are essential to achieving sustainable governance performance.